Buoyancy effects in boundary layers on a continuously moving vertical surface with a parael free stream (Archives of Mechanics - Test, 2001)
An analysis is performed to study the effect of the buoyancy force on the flow and heat transfer characteristics in a viscous fluid over a heated vertical continuously moving surface with a parallel free stream. The buoyancy force varies with the streamwise distance x and hence introduces nonsimilarity in the flow field. Both the constant wall temperature and constant heat flux conditions are included in the analysis. The partial differential equations governing the flow are solved numerically. Closed form solutions are obtained when the wall and free stream velocities are equal and there is no buoyancy force. Also the correlation equations for the local Nusselt number are developed. It is found that for opposing flow or for an upstream moving wall, the solution does not exist beyond a certain value of the buoyancy parameter or the ratio of wall and free stream velocities.